The Worker Role Interview -- preliminary data on the predictive validity of return to work of clients after an insurance medicine investigation. - Ekbladh E; Haglund L; Thorell L (Journal of Occupational Rehabilitation, 2004)
The aim was to investigate the predictive validity of the Worker Role Interview (WRI) for return to work at a 2-year follow-up of clients who attended an insurance medicine investigation center. The WRI identifies psychosocial and environmental factors that influence a person's abilities to return to work. Forty-eight of 202 consecutively selected clients constituted the study group. The Mann-Whitney U test was used to test the statistically significant differences in WRI ratings between those who were working (n = 6) and those who were not (n = 42) 2 years after their investigations. Five of the 17 items in WRI had a tentative predictive validity of return to work. The content area 'personal causation' in WRI, had the best predictive validity. The results emphasize the importance of considering the unique individual's beliefs and expectations of his/her effectiveness at work when assessing clients' work ability and planning for further rehabilitation.